2000
DOI: 10.13181/mji.v9i3.634
|View full text |Cite
|
Sign up to set email alerts
|

Hospital based cancer registry in Cipto Mangunkusumo hospital Jakarta

Abstract: telah dimu/ai tahun 1997, bertujuan untuk memberi data bagi program pengendalian kanker dan membanlu perencanaan rumah sakit. Maka/ah ini menyajikan registrasi kanker sepanjang tahun 1997-1998. Data dari semua pasien kanker yang baru terdiagnosis dicatat pada Formulir Registrasi Kanker. Yang didata ialah identitas pasien, demografi dan kultur, penilaian tumor dan usia, serta penatalaksanaan. Terdapat 2144 (0.48%) penderita kanker diantara 444.178 pasien baru yang berobat ke RSCM. Perbandingan perempuan dan lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Age distribution showed that the most prevalent age group of cancer patients at RSCM is 45-54 year-old, older than data from 1997-1998 which was 35-44 year-old. 4 The transition is similar with epidemiological trend worldwide. 6 The worldwide cancer trend, which correlates to western lifestyle, such as breast, prostate, endometrial, and other cancers, would increase as the age increases.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Age distribution showed that the most prevalent age group of cancer patients at RSCM is 45-54 year-old, older than data from 1997-1998 which was 35-44 year-old. 4 The transition is similar with epidemiological trend worldwide. 6 The worldwide cancer trend, which correlates to western lifestyle, such as breast, prostate, endometrial, and other cancers, would increase as the age increases.…”
Section: Discussionsupporting
confidence: 66%
“…The ratio between men and women is in accordance with the data published by Globocan 5 in 2012, which stated that the number of cancer patients in Southeast Asia for five years was 1237 for men and 2041 for women. 5 Compared with the data from 1997-1998, 4 the ratio was still consistent, albeit a slight difference. In 2013 HBCR ratio for women and men was 3:2, whereas in 1997 the ratio was 17:10 for women and men.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…13 In addition, HBCR data from Cipto Mangunkusumo Hospital in 1997-1998 by Sibuea et al also supports this finding. 14 In ovarian cancer, the most common morphological classification was malignant neoplasms which cover about 18.7%. Meanwhile, as many as 22.02% of cases have unknown morphological status.…”
Section: Discussionmentioning
confidence: 99%